LigDig: a web server for querying ligand-protein interactions - Fuller, Jonathan C.; Martinez, Michael; Henrich, Stefan; Stank, Antonia; Richter, Stefan; Wade, Rebecca C. (Bioinformatics, 2015)
LigDig is a web server designed to answer questions that previously required several independent queries to diverse data sources. It also performs basic manipulations and analyses of the structures of protein–ligand complexes. The LigDig webserver is modular in design and consists of seven tools, which can be used separately, or via linking the output from one tool to the next, in order to answer more complex questions.
Advance access publication date: 29 November 2014
Gesehen am 09.10.2020